Defect‐Engineered Nanozyme‐Linked Receptors. Issue 33 (5th July 2021) - Wu, Yu; Wen, Jing; Xu, Weiqing; Huang, Jiajia; Jiao, Lei; Tang, Yinjun; Chen, Yifeng; Yan, Hongye; Cao, Shiyu; Zheng, Lirong; Gu, Wenling; Hu, Liuyong; et al.
Abstract: Though nanozymes are successfully applied in various areas, the increasing demands facilitate the exploitation of nanozymes possessing higher activity and more functions. Natural enzyme‐linked receptors (ELRs) are critical components for signal transductions in vivo by expressing activity variations after binding with ligands. Inspired by this, the defect‐engineered carbon nitrides (DCN) are reported to serve as nanozyme‐linked receptors (NLRs). For one thing, cyano defects increase the enzyme‐like activity by a factor of 109.5. For another, DCN‐based NLRs are constructed by employing cyano groups as receptors, and variable outputs are ensued upon the addition of ion ligands. Significantly, both the cascade effect and electronic effect are demonstrated to contribute to this phenomenon. Finally, NLRs are used for pattern recognition of metal ions, indicating the signal transduction ability of NLRs as well. This work not only provides great promise of defect engineering in nanozymes, but also contributes to the design of artificial ELRs. Abstract : Defect engineering is reported to synthesize defective carbon nitride as peroxidase mimic. The defects not only remarkably increase the catalytic activity, but also serve as receptors to mimic the function of enzyme‐linked receptors. This work highlights the mimicking of both enzymatic activity and function by defect‐engineered nanozymes, which may further shorten the gap between nanozymes and enzymes.